Automatic feeders for Nile tilapia raised in cages: productive performance at high feeding frequencies and different rates - Oliveira, F. A. [UNESP]; Argentim, D. [UNESP]; Novelli, P. K. [UNESP]; Agostinho, S. M. M.; Agostinho, L. M. [UNESP]; Agostinho, C. A. [UNESP] (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2016)
The main goal of modern intensive fish farms should be to increase productivity at a low cost. The automation of fish feeding plays an important role in this scenario since it may improve feed efficiency and reduce organic waste emissions. The aim of this experiment was to provide basic information for the development of feeding techniques using automatic feeders. The experiment was done from September to December, with tilapia weighing 185g, fed 48 meals a day at 22 or 30 minute intervals, with feeding rates of 2, 3 and 4% of live weight. Eighteen 1m(3) net cages equipped with automatic feeders were distributed in one pond. During the experimental trial the mean values for dissolved oxygen, pH and temperature were 3.20mg/l, 8.03 and 25.43 degrees C, respectively. The highest average weight of 683.73g was achieved for fish treated with 4% of live weight at 30 minute intervals between meals. There was no difference for viscero-somatic index, demonstrating no alteration in the final carcass quality. These results demonstrate that a higher feeding rate added to efficient feed management can be used at the final stages of raising Nile tilapia in cages without compromising final fish productive quality.
Keywords: automatic feeding; feeding management; Oreochromis niloticus; feed efficiency; carcass indexes